Implementation of Motor Function Measure score percentile curves - Predicting motor function loss in Duchenne muscular dystrophy. (January 2022) - Hafner, Patricia; Schmidt, Simone; Schädelin, Sabine; Rippert, Pascal; Hamroun, Dalil; Fabien, Solenn; Henzi, Bettina; Putananickal, Niveditha; Rubino-Nacht, Daniela; Vuillerot, Carole; Fischer, Dirk; ,; et al.
Abstract: The Motor Function Measure is a standardized scoring system to evaluate motor function and monitor disease progression in neuromuscular diseases such as Duchenne muscular dystrophy. There are no available reference percentile curves for this measure. The aim of this analysis was to generate Motor Function Measure percentile curves for ambulant and non-ambulant patients affected by Duchenne Muscular Dystrophy, providing the opportunity to better evaluate the status and progression of an individual patient compared to other patients in the same age group. Data of patients aged between 6 and 15 years (819 measurements) was obtained from the international Motor Function Measure database. Age-dependent percentile curves were estimated using a "Generalized additive model for location, scale and shape" as suggested by the World Health Organisation Multicentre Growth Reference Study Group. Percentile curves for the Motor Function Measure total score and its sub-scores for patients with and without treatment with glucocorticoids are presented. Mean scores decline with age. Patients treated with glucocorticoids have higher mean values compared to glucocorticoid-naïve patients at the same age. The percentile curves with the online tool extend the clinical utility of the Motor Function Measure by facilitating the interpretation of individual standing and disease progression. Highlights: MFM percentile curves are useful to evaluate individual disease progression. Clinical research will be facilitated by choosing patients with similar curses. Treatment effects can be visualised. Smaller trials will be informative by increased effect sizes.